CAEC (COMMUNITY OF ACTIVE ENGLISH COMMUNICATION)-BASED EMPOWERMENT OF LAKE TEMPE WAJO TOURISM REGIONAL COMMUNITIES - Syahrun Adzim; Amiruddin Amiruddin (Perkumpulan Dosen Muslim Indonesia, 2021)
South Sulawesi's Lake Tempe is a popular tourist site. Many foreigners, both locally and internationally, visit Lake Tempe. The quality of the guide's service has a significant impact on the smoothness and comfort of travel in Tempe. As a result, a training and mentoring program for foreign-language tourism performers in the Tempe Lake area is required. The PKM program is carried out in stages: (1) PKM participant selection; (2) PKM briefing participants; (3) survey site; (4) PKM program socialization; (5) debriefing tourist actors; and (6) twice-weekly training and mentorship for three months. In total, 25 meetings were held to provide training and mentorship. The training team enhances the vocabulary at the start of the training, and subsequently, the material and speaking are intensified by the team. The assessment's findings revealed a significant increase: (1) There were three people in the very good group, 25 in the good category, and two in the bad category when it came to vocabulary ability. (2) There are 26 persons who are classified as good at tenses, and just four people who are classified as less good. (3) In terms of speaking skill, four people were rated as very good, 25 were rated as good, and one was rated as less good.